Effect of a home-made pollen substitute on honey bee colony development - Van Der Steen, J.
In 2001 and 2002, studies were conducted on a pollen substitute formulated for easy home preparation. Tests were done with free flying honey bee colonies. In 2001, pollen supply was restricted with pollen traps in 9 experimental colonies. Colonies were then equally divided among three treatments: (1)fed pollen substitute, (2)fed bee-collected bee bread, or (3)no supplement. In 2002 the design was similar except that the bee bread treatment was replaced with a control treatment without pollen trap or supplements. The pollen substitute was readily consumed by bees, and brood development (fraction of larvae achieving pupa)did not differ among treatments. In 2002, longevity of bees was highest in colonies fed pollen substitute even though this group had a pollen trap. The average concentration of haemolymph protein did not differ among treatments in 2001, but in 2002 this value was significantly highest in colonies without a pollen trap. The results of this study are applicable for honey bee colonies placed in greenhouses where pollen deficiency negatively affects bee longevity, brood rearing and pollination efficacy.
Keywords: POLLEN SUBSTITUTE; PROTEIN; LONGEVITY; APIS MELLIFERA L